2018
DOI: 10.3389/fnins.2018.00705
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Affect Decision Criteria During Recognition Memory With Continuous Theta Burst Stimulation

Abstract: A decision criterion establishes the minimum amount of memory evidence required for recognition. When a liberal criterion is set, items are recognized based on weak evidence whereas a conservative criterion requires greater memory strength for recognition. The decision criterion is a fundamental aspect of recognition memory but little is known about the underlying neural mechanisms of maintaining a criterion. We used continuous theta burst stimulation (cTBS) with the goal of inhibiting prefrontal cortex excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Although criterion shifting tendencies are quite stable within people, there are vast individual differences across people (Aminoff et al, 2012, 2015; Frithsen et al, 2018; Kantner et al, 2015; Layher et al, 2018; Miller & Kantner, 2020). Individual differences in strategic criterion shifting do not appear to be a result of an inability for certain people to shift criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although criterion shifting tendencies are quite stable within people, there are vast individual differences across people (Aminoff et al, 2012, 2015; Frithsen et al, 2018; Kantner et al, 2015; Layher et al, 2018; Miller & Kantner, 2020). Individual differences in strategic criterion shifting do not appear to be a result of an inability for certain people to shift criteria.…”
Section: Discussionmentioning
confidence: 99%
“…If people are unaware of the advantages for shifting criteria, criterion shifts are generally not observed (Rhodes & Jacoby, 2007; Verde & Rotello, 2007). When people are made aware of the advantages for shifting, the extent of criterion shifting increases on average , but analyses of individual differences reveal that this is not true for everyone (Aminoff et al, 2012, 2015; Frithsen et al, 2018; Kantner et al, 2015; Layher et al, 2018; Miller & Kantner, 2020). Our studies revealed that these individual differences in criterion shifting behavior are remarkably consistent across multiple testing sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decades, a plethora of studies have investigated behavioral changes after transcranial magnetic stimulation (TMS, for reviews see e.g., Pascual-Leone et al, 2000;Rushworth and Taylor, 2006;Koch and Rothwell, 2009;Rossini et al, 2010;Crivelli and Balconi, 2017;Klaus and Schutter, 2018). Although brain stimulation is a promising approach to study the causal relationship and close the explanatory gap between brain function and behavior, it has its drawbacks as exemplified in interpreting behavioral null results after stimulation (e.g., Rossi et al, 2006;Zanto et al, 2013;Gohil et al, 2016;Bor et al, 2017;Engelen et al, 2018;Layher et al, 2018;Lopez-Alonso et al, 2018;Codol et al, 2020;see also De Graaf and Sack, 2011). There are a number of possible explanations for TMS null results ranging from the stimulated brain region not being causally involved in the tested behavior (Rossi et al, 2006;Gohil et al, 2016) to dynamic brain network changes compensating for the stimulation (Lee et al, 2003;O'Shea et al, 2007;Zanto et al, 2013;Hartwigsen, 2018).…”
Section: Introductionmentioning
confidence: 99%